1996
DOI: 10.1021/la951005q
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Structural Transformation of Aggregated Al13 Polycations, Promoted by Salicylate Ligand

Abstract: The chemical and structural consequences of the interaction between aggregates made of Al13 polycations and salicylate ligand were examined using adsorption isotherms, electrophoresis, infrared spectroscopy, Fraunhofer light diffraction, and static light scattering spectroscopy. Drastic changes were observed for a pseudo equilibrium ligand concentration equimolar to Al13. Below this concentration, salicylate forms monodentate complexes with the charged aluminum sites, decreasing the electrostatic repulsion bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…Therefore, Al 13 polymers and aluminum polycations with a Al VI /Al IV < 12, are the dominating species within dialyzed coagulated MHS. Previous reports indicated that low molecular weight organic acids hinder aluminum hydrolysis (Masion et al, 2000) and depolymerize preformed Al 13 polycations (Molis et al, 1996;Amirbahman et al, 2000). Our results suggest that, in the OCC range and in the timescale of the experiment, the Al 13 coagulant species seem to be stable in presence of MHS, which is consistent with previous evidence of Al 13 polycations found in organic soil horizons (Hunter and Ross, 1991).…”
Section: Resultssupporting
confidence: 91%
“…Therefore, Al 13 polymers and aluminum polycations with a Al VI /Al IV < 12, are the dominating species within dialyzed coagulated MHS. Previous reports indicated that low molecular weight organic acids hinder aluminum hydrolysis (Masion et al, 2000) and depolymerize preformed Al 13 polycations (Molis et al, 1996;Amirbahman et al, 2000). Our results suggest that, in the OCC range and in the timescale of the experiment, the Al 13 coagulant species seem to be stable in presence of MHS, which is consistent with previous evidence of Al 13 polycations found in organic soil horizons (Hunter and Ross, 1991).…”
Section: Resultssupporting
confidence: 91%
“…In this study, salicylic acid and Al 13 species in the PACl 2 immediately formed Al 13 -salicylate complexes. Similar results obtained by Molis et al [37] indicated the presence of salicylate-Al 13 surface complex by infrared spectroscopy.…”
Section: Effect Of Organic Matter On Al Speciationsupporting
confidence: 88%
“…Using this standard method, the resulting solution will contain 90-95 % of the polycation Al 13 . In fact, many studies using the nuclear magnetic resonance spectroscopy (NMR), provided the proof of its existence and allowed the aluminum speciation [40][41][42][43][44][45][46] .…”
Section: Preparation Of Al 13mentioning
confidence: 99%